Relationship between skin temperature and blood flow during exposure to radio frequency energy: implications for device development - Georgia E. H. Robles; David A. Nelson (BMC Biomedical Engineering)
Abstract Background The ST response to high frequency EM heating may give an indication of rate of BF in underlying tissue. This novel method, which we have termed REFLO (Rapid Electromagnetic Flow) has potential for applications such as detection of PAD. The method utilizes the relationship between blood flow rate and tissue temperature increase during exposure to radio frequency (RF) energy. We are developing an REFLO device to screen for peripheral artery disease (PAD). PAD is characterized by impaired blood flow to the legs, as reflected in the skin microcirculation. The REFLO system incorporates a radio frequency transmitter and a compact transducer housing a micropatch antenna and an infrared (IR) temperature sensor. At high RF frequencies (> 6 GHz) tissue heating is confined to the skin, such that an indication of blood flow may be inferred from the temperature response to controlled heating. The objective of this study is to determine the extent to which the magnitude and depth of heating as well as device sensitivity are functions of (i) RF frequency and (ii) thickness of the dermal tissue layer. Results Results show that it is feasible to measure blood flow rate with REFLO technology. Surface temperature increases were found to be more dependent upon the magnitude of power absorption than location of absorption within the skin. While surface temperature response does depend upon radio wave frequency and thickness of the dermis layer, such dependencies are mild. Sensitivity to blood flow rate was found to be proportional to the magnitude of absorbed power. Conclusion Results show that it is feasible to discriminate between blood flow rates using REFLO technology at frequencies within the 10–94 GHz range. All frequencies analyzed produced similar levels of sensitivity to blood flow rate despite significant differences in penetration depth. These results are being used in the development of a preclinical prototype for quick and easy detection of asymptomatic PAD in humans.